ChemInform Abstract: 1, 2, 3‐Triazoles as Versatile Directing Group for Selective sp2 and sp3 C—H Activation: Cyclization vs. Substitution. Issue 7 (18th February 2014) - Ye, Xiaohan; He, Zhengrong; Ahmed, Tonia; Weise, Keith; Akhmedov, Novruz G.; Petersen, Jeffrey L.; Shi, Xiaodong
Abstract The choice of the substitution pattern of the triazole‐containing directing group determines whether a substitution or cyclization takes place.